한국 근로자의 근로생애주기별 사고경험률 - 조교영; 최은숙; 권민정; 이창훈 (한국직업건강간호학회지, 2018)
Purpose: In this study, we attempted to analyze the occupational accident experience rate by working life cycle of Korean workers considering entrance and turnover in their jobs. The specific goal of this study was to calculate the accident experience rate according to workers' turnover history and previous accident experience. Methods: We constructed a cumulative data set of 90,338 cases of workers' accident experiences in their jobs from the Fourth Korean Working Conditions Survey. The accident experience rates according to workers' turnover and previous accident experiences were analyzed using descriptive statistics and analysis of variance. Results: In this study, the cumulative accident experience rate of Korean workers was found to be 5.2%. It was confirmed that the accident experience rate of workers increased as the turnover frequencies increased. In addition, we analyzed only the data of the workers who had experienced turnover and found that the accident experience rate after turnover increased about 7.5 times when workers had experienced accidents in the past. Conclusion: To prevent occupational accidents in workers, safety strategies should consider a worker's previous job history and injury experiences. It will also be necessary to focus preventive efforts on new and young workers through ongoing monitoring and on-the-job training.